Employee perceptions of individual green HRM practices and voluntary green work behaviour: a signalling theory perspective. (23rd June 2022) - Garavan, Thomas; Ullah, Irfan; O'Brien, Fergal; Darcy, Colette; Wisetsri, Worakamol; Afshan, Gul; Mughal, Yasir Hayat
Abstract : Green human resource management (GHRM) practices increasingly receive attention by both HRM scholars and practitioners. Research on these practices has emphasised systems rather than individual HR practices and HR managers' perceptions rather than employees' perceptions of these practices. In addition, little attention has been paid to the mediating mechanisms that link employee perceptions of GHRM practices to voluntary green work behaviour (VGWB) outcomes. This study addresses these research gaps by investigating the impact of employee perception of four individual GHRM practices – recruitment, selection, performance management and compensation – and their impact on employee VGWB in Chinese manufacturing firms. We also investigate the mediating role of reflective moral attentiveness (RMA). Applying signalling theory and drawing on data collected from 300 employees in 50 manufacturing organisations, we found a direct relationship between all four individual GHRM practices and VGWB. We also found that RMA partially mediated the relationship between selection, performance management and compensation practices (but not recruitment) and VGWB. We discuss the theoretical and practical implications of our study findings.